The Physicochemical Properties, Antioxidant Potential, and Skin Penetration of Pterostilbene-Loaded NLCs - Louise, Elaine; Yen, Feng-Lin (Indonesian Journal of Life Sciences, 2026)
Pterostilbene is a naturally occurring polyphenolic compound known for its antioxidant activity and potential use in topical skin care formulations. However, its poor water solubility and limited skin penetration reduce its therapeutic effectiveness. In this study, pterostilbene-loaded nanostructured lipid carriers (PT-NLCs) were developed and evaluated as a topical delivery system to enhance its stability and dermal performance. The PT-NLCs showed a mean particle size of 78–99 nm (88.57 ± 10.60 nm), a polydispersity index of 0.284, and an encapsulation efficiency of 99.98%, indicating a stable nanosystem. The NLC formulation increased apparent water solubility by over 5,000-fold and improved skin penetration by approximately 360% compared with raw pterostilbene. PT-NLCs also demonstrated enhanced antioxidant activity, with about a 34% increase in radical scavenging capacity in the DPPH assay and improved protection of skin cells against oxidative stress while maintaining good cytocompatibility. These findings demonstrate that NLC-based encapsulation effectively improves the solubility, dermal penetration, and antioxidant efficacy of pterostilbene, highlighting its potential as a promising ingredient for topical skin treatment applications.